Determinants of employee engagement among assistant registrars of public universities in Malaysia and moderating effect of age, gender and length service - Ruswahida Ibnu Ruslan (School of Business Innovation & Technopreneurship, 2017)
This research attempts to investigate within the following scopes: This study is a quantitative in nature and the samples were collected at one time (cross-sectional), specifically from twenty public universities in Malaysia. In short, private universities are not involved based on these following reasons. First, the issue of budget allocation from government. Private universities with the application of market principle in their operation and management may or may not receive budget allocation from the government. Nevertheless, unlike public universities, most of the private universities are profit orientated. Fees are charged for cost recovery and approximately five to ten times higher than public universities (Sirat, 2005). The objectives, functioning, funding and modus operandi of private universities are different from public universities (Gupta, 2008). In brief, the survival of private universities depend on their ability to innovate and experiment with different kinds of study programmes that require a large budget and resource allocation (Lee, 2004). Thus, because of the goals of universities are different, the job scope of the staffs also will differ according to the universities' needs. Based on these differences, only public universities were selected.